Pendidikan Islam Inklusif dan Bermakna: Telaah Tafsir Tarbawi Q.S ‘Abasa 1-10 atas Upaya Pembentukan Karakter Anak Berkebutuhan Khusus di SD Roushon Fikr Jombang - Umirul Musyarofah; Devi Rofidah Celine; Firdaus Ulul Absor; Naila Nafahatus Sahariyah Al-Ulya; Muhammad Shodiq (Pekerti: Journal Pendidikan Islam dan Budi Pekerti, 2025)
This study aims to explore the implementation of Islamic character education for students with special needs (ABK) at SD Islam Roushon Fikr Jombang based on the tafsir tarbawi perspective of Surah ‘Abasa [80]: 1–10. These verses serve as a significant theological foundation emphasizing the value of honoring every human being regardless of physical or mental limitations. This research employs a qualitative descriptive approach through field study methods. Data were collected through observation, in-depth interviews with special education teachers (GPK), the school principal, and analysis of school curriculum documents. The findings reveal that the school integrates Islamic character values such as patience, compassion, sincerity, empathy, responsibility, and tolerance into the learning process for ABK students. Each of the 13 students with special needs is accompanied by a dedicated teacher who applies an individualized and need-based approach. The inclusive and humanistic learning environment is supported by regular religious activities such as salat dhuha, communal dhikr, and daily gratitude reflections. Islamic storytelling and the delegation of small responsibilities to ABK students also help foster trustworthiness and independence. The tafsir tarbawi interpretation of Surah ‘Abasa reinforces a fair and inclusive pedagogical orientation, placing human dignity at the core of Islamic education. As a result, SD Islam Roushon Fikr has successfully developed a model of character education that is not only religiously grounded but also inclusive and appreciative of diversity, in alignment with the spirit of rahmatan lil ‘alamin. This study contributes to the development of applicable Islamic character education models for other inclusive educational institutions.